The Application of Hybrid Contract Concept in Ijarah Muntahiyah Bittamlik (IMBT) Product - Abduloh, Ade; Herdiana, Nana; Prasetyo, Yoyok (Zona Law And Public Administration Indonesia, 2024)
This paper reviews the important role of hybrid contracts in the sharia finance industry, focusing on a case study of Ijarah Muntahiyah Bittamlik (IMBT) based on the views of scholars and DSN MUI regulations. An analytical descriptive approach is used to identify various types of hybrid contracts as well as highlighting the scholars' perspectives on IMBT. The results of this study clarify the concept of hybrid contract as a combination of two or more contracts that are considered as a whole unit. Furthermore, this study analyzes how IMBT is applied in Islamic banking practices and how scholars view its legal status. This research emphasizes the importance of understanding the complexities and implications of the use of hybrid contracts in the context of Islamic economic jurisprudence. Taking into account the differing views, the research highlights the need for clarity in the use of hybrid contracts, by ensuring that their implementation is in line with established sharia principles. The conclusion emphasizes the importance of an in-depth understanding of hybrid contracts in the context of the shariah finance industry as well as the need for a clear regulatory framework to ensure integrity and compliance in shariah finance practices.